Photothermal Therapy: pH‐Responsive Cyanine‐Grafted Graphene Oxide for Fluorescence Resonance Energy Transfer‐Enhanced Photothermal Therapy (Adv. Funct. Mater. 1/2015). (January 2015) - Guo, Miao; Huang, Jie; Deng, Yibin; Shen, He; Ma, Yufei; Zhang, Mengxin; Zhu, Aijun; Li, Yanli; Hui, He; Wang, Yangyun; Yang, Xiangliang; Zhang, Zhijun; et al.
<x xml:space="preserve">Abstract</x> On page 59, Z. J. Zhang, H. B. Chen, and co‐workers explore a pH‐responsive photothermal nanoconjugate, in which grafted cyanine dye acts as the donor of near‐infrared fluorescence (NIRF) and graphene oxide with broad NIR absorbance and effective photothermal conversion efficiency is selected as a typical receptor of fluorescence resonance energy transfer (FRET), for enhanced photothermal therapy with tumor ablation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>